Prevalence of falls and its associated factors among elderly in Kota Bharu, Kelantan : results from the elderly health screening program - Esa, Wafaak (2015)
Population ageing is taking place globally including in Malaysia. Prevalence of obesity among the elderly is also increasing worldwide. Falls among the elderly lead to morbidity, mortality and is also an economic burden. The aim of this cross sectional study was to determine the prevalence of falls among the elderly and its associated factors especially of body mass index factor among elderly who participated in a health screening program between January and December 2014 in Kota Bharu, Kelantan. Data were obtained from the health screening form from all government health clinics in Kota Bharu. There were 434 elderly who fulfilled the inclusion and exclusion criteria. A whole population sampling was employed. The descriptive and multiple logistic regression was applied to answer the objectives of the study. The results showed that the prevalence of falls among elderly who participated in the health screening program was 23.3% (95% CI 0.19, 0.27). This study demonstrated that falls was associated with obesity (OR adj 2.55, 95% CI: 1.15, 5.68; p= 0.021). Other significant associated factors of falls were age more than 80 years old (OR adj 36.14, 95% CI: 9.06, 144,13; p<0.001), being female (OR adj 0.48, 95% CI: 0.25, 0.93; p= 0.030), being employed (OR adj 0.05, 95% CI: 0.07, 0.29; p=0.001), symptoms of dizziness (OR adj 6.90, 95% CI: 1.36, 35.06; p=0.020) imbalance and instability (OR adj 11.65, 95% CI: 3,65, 37.20; p<0.001), polypharmacy (OR adj 4.18, 95% CI: 1.46, 12.00 ; p=0.008) and high waist circumference (OR adj 2.42, 95% CI: 1.22, 4.80; p=0.011). This study demonstrated that the prevalence of falls among elderly is still an issue and its associated factors especially obesity should be intervened.